Oxytocin Receptor Polymorphism Is Associated With Sleep Apnea Symptoms - Goto, Hisanori; Yamamoto, Yasuhiko; Tsujiguchi, Hiromasa; Sato, Takehiro; Yamamoto, Reina; Takeshita, Yumie; Nakano, Yujiro; Kannon, Takayuki; Hosomichi, Kazuyoshi; Suzuki, Keita; Nakamura, Masaharu; Kambayashi, Yasuhiro; et al. (Journal of the Endocrine Society, 2024)
Abstract Context Oxytocin supplementation improves obstructive sleep apnea (OSA), and animal studies suggest involvement of oxytocin in respiratory control. However, the relationship between endogenous oxytocin signaling and human sleep status remains undetermined. Objective In this study, we approached the contribution of the intrinsic oxytocin-oxytocin receptor (OXTR) system to OSA by genetic association analysis. Methods We analyzed the relationship between OXTR gene polymorphisms and sleep parameters using questionnaire data and sleep measurements in 305 Japanese participants. OSA symptoms were assessed in 225 of these individuals. Results The OXTR rs2254298 A allele was more frequent in those with OSA symptoms than in those without (P = .0087). Although total scores on the Pittsburgh Sleep Quality Index questionnaire did not differ between the genotypes, breathlessness and snoring symptoms associated with OSA were significantly more frequent in individuals with rs2254298 A genotype (P = .00045 and P = .0089 for recessive models, respectively) than the G genotype. A multivariable analysis confirmed these genotype-phenotype associations even after adjusting for age, sex, and body mass index in a sensitivity analysis. Furthermore, objective sleep efficiency measured by actigraph was not significantly different between genotypes; however, subjective sleep efficiency was significantly lower in the rs2254298 A genotype (P = .013) compared with the G genotype. The frequency of the A allele is higher in East Asians, which may contribute to their lean OSA phenotype. Conclusion The OXTR gene may contribute to OSA symptoms via the respiratory control system, although it could be in linkage disequilibrium with a true causal gene.